Now you hear it: a predictive coding model for understanding rhythmic incongruity. Issue 1 (23rd April 2018) - Vuust, Peter; Dietz, Martin J.; Witek, Maria; Kringelbach, Morten L.
Abstract: Rhythmic incongruity in the form of syncopation is a prominent feature of many contemporary musical styles. Syncopations afford incongruity between rhythmic patterns and the meter, giving rise to mental models of differently accented isochronous beats. Syncopations occur either in isolation or as part of rhythmic patterns, so‐called grooves . On the basis of the predictive coding framework, we discuss how brain processing of rhythm can be seen as a special case of predictive coding. We present a simple, yet powerful model for how the brain processes rhythmic incongruity: the model for predictive coding of rhythmic incongruity. Our model proposes that a given rhythm's syncopation and its metrical uncertainty (precision) is at the heart of how the brain models rhythm and meter based on priors, predictions, and prediction error. Our minimal model can explain prominent features of brain processing of syncopation: why isolated syncopations lead to stronger prediction error in the brains of musicians, as evidenced by larger event‐related potentials to rhythmic incongruity, and why we all experience a stronger urge to move to grooves with a medium level of syncopation compared with low and high levels of syncopation.